2016
DOI: 10.1007/s00213-016-4488-2
|View full text |Cite
|
Sign up to set email alerts
|

Scopolamine disrupts place navigation in rats and humans: a translational validation of the Hidden Goal Task in the Morris water maze and a real maze for humans

Abstract: In the task based on the MWM, scopolamine impaired place navigation, while co-administration of donepezil alleviated this effect in comparable animal and human protocols. Using scopolamine and donepezil to challenge place navigation testing can be studied concurrently in animals and humans and may be a valid and reliable model for translational research, as well as for preclinical and clinical phases of drug trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 58 publications
3
18
0
Order By: Relevance
“…The authors reported successful validation of the tasks and scopolamine, as no significant differences were found between the human volunteers and the animals. Donepezil was shown to exhibit some ameliorative effect; however, this was not clear in all cases ( 80 ).…”
Section: Antimuscarinic Agents In Spatial Tasksmentioning
confidence: 96%
See 1 more Smart Citation
“…The authors reported successful validation of the tasks and scopolamine, as no significant differences were found between the human volunteers and the animals. Donepezil was shown to exhibit some ameliorative effect; however, this was not clear in all cases ( 80 ).…”
Section: Antimuscarinic Agents In Spatial Tasksmentioning
confidence: 96%
“…Scopolamine-induced cognitive impairment has also been shown to possess good validity as a translational model in research. Laczó et al ( 80 ) compared the effects of scopolamine administration (as well as its coadministration with donepezil, an AChE inhibitor) in rats and humans in the MWM and the Hidden Goal Task, an analog of the water maze fit for use in humans. The authors reported successful validation of the tasks and scopolamine, as no significant differences were found between the human volunteers and the animals.…”
Section: Antimuscarinic Agents In Spatial Tasksmentioning
confidence: 99%
“…A 3-month openlabel study has shown that a computerized human analogue of the Morris water maze has the potential to measure the effects of donepezil in mild AD 145 . Subsequent research has shown that the disruptive effect of scopolamine on place navigation can be reverted by donepezil, a finding that was demonstrated using both rodent and human versions of the Morris water maze 146 .…”
Section: [H1] Conclusionmentioning
confidence: 98%
“…While at T1, a paper version of the supermarket map was used to record responses, an alternative form of the VST was employed 18 months later at T2, to facilitate electronic and automatic recording of participant responses on a 9.7inch iPad. VST trials (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) in both versions were identical. At T2, the scoring parameter for VST allocentric memory was updated to include the exact distance of error (here referred to as map drop error), with the specific aim of increasing the sensitivity of the VST sub-measure to measure spatial memory impairment.…”
Section: Methodsmentioning
confidence: 93%
“…Spatial navigation shows promise as an outcome measure for preclinical Alzheimer disease (AD) in drug treatment trials, but it's test-retest reliability is not clear [1][2][3][4]. Drug development for AD has been plagued by the failure of cognitive outcomes measures to detect treatment response due to i) insufficient sensitivity and specificity for preclinical neuropathology and/or ii) poor test-retest reliability, both of which can mask neural response to treatment [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%